PENGARUH KERAGAMAN MENU, KEUNIKAN PRODUK DAN CITA RASA TERHADAP KEPUTUSAN PEMBELIAN PADA WARUNG LESEHAN SAMBEL IJO ILHAM RAJABASA DI SAWOO PONOROGO - Nistirohah Nur Fitriani; Adi Santoso; Fery Setiawan (Jurnal AKTUAL, 2022)
This study aims to determine the effect of menu diversity, product uniqueness, and taste on purchasing decisions at warung lesehan sambel ijo ilham rajabasa in sawoo. The method used in this study is a quantitative method. Types of data from this study were obtained though distributing quetionnaires to respondent and analyzed SPSS 2022 aplication. The popolation and samples in this study indicate that: 1) there is an influence between menu diversity on purchasing decisions at warung lesehan sambel ijo in Sawoo Ponorogo. 2) there is an influence between the uniqueness of the product on purchasing decisions at warung lesehan sambel ijo in Sawoo Ponorogo. 3) there is an influence between taste in purchasing decisions at warung lesehan sambel ijo in Sawoo Ponorogo. 4) there is an influence between menu diversity, product uniqueness, and taste on purchasing decisions at warung lesehan sambel ijo in sawoo Ponorog.